Lacunicambarus dalyae: a new species of burrowing crayfish (Decapoda: Cambaridae) from the southeastern United States - Glon, Mael G.; Williams, Bronwyn W.; Loughman, Zachary J. (Zootaxa, 2019)
The Jewel Mudbug, Lacunicambarus dalyae sp. nov., is a large, colorful primary burrowing crayfish found in Alabama, Florida, Georgia, Mississippi and Tennessee. This species is most similar in appearance to the Paintedhand Mudbug, L. polychromatus, a species found across the Midwestern United States. The ranges of the two species overlap minimally, and they can be distinguished from each other based on several characters, the most notable of which is the much longer central projection of the gonopod in Form I and II males of L. dalyae sp. nov. relative to L. polychromatus. Like its congeners, L. dalyae sp. nov. is commonly found in burrows in the banks and floodplains of streams and is resilient to a moderate amount of anthropogenic habitat degradation, being occasionally collected from burrows in roadside ditches and urban lawns.